PENERAPAN METODE FUZZY SIMPLE ADDITIVE WEIGHTING (SAW) UNTUK PENGANGKATAN KARYAWAN KONTRAK PADA PT. ARANAD KARYA SARANATAMA - Ade Ajeng Gusti Pratiwi; Laila Septiana; Irawan Satriadi (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2018)
Human Resources (HR) is one of the valuable assets owned by each company. HR management requires a clear standardization in order to contribute positively to a company or organization. In terms of recruitment, the company needs to do HR planning in order to meet the demand for human resources. The main objective of the process of hiring a permanent employee contract that is to get the right people who meet certain requirements to fill the positions that are necessary, so that the person is able to work optimally and can survive in the company for a long time. In the system of appointment of contract workers into permanent employees of PT. Aranad work Saranatama implement some of the things the possibility of an employee or the terms of the contract can become permanent employees at PT. Aranad Saranatama work, one that the company is indeed in need of an employee, as well as the desire of a contract employee to work as a permanent employee in PT. Aranad Saranatama work. Because of it, not all contract employees can become permanent employees there should be the selection of a leader of the company to be able to accept an employee in the company.